The multifaceted roles of metabolic enzymes in the Paracoccidioides species complex - Marcos, Caroline M.; Oliveira, Haroldo C. de; da Silva, Julhiany de F.; Assato, Patrícia A.; Fusco-Almeida, Ana M.; Mendes-Giannini, Maria J. S. (Frontiers in Microbiology, 2014)
Paracoccidioides species are dimorphic fungi, and are the etiologic agents of paracoccidioidomycosis (PCM), a serious disease of multiple organs. The large number of tissues colonized by this fungus suggests the presence of a variety of surface molecules involved in adhesion. A surprising finding is that the majority of enzymes in the glycolytic pathway, tricarboxylic acid (TCA) cycle and glyoxylate cycle in Paracoccidioides spp. has adhesive properties that aid in the interaction with the host extracellular matrix, and so act as ‘moonlighting’ proteins. Moonlighting proteins have multiple functions and add another dimension to cellular complexity, while benefiting cells in several ways. This phenomenon occurs in both eukaryotes and prokaryotes. For example, moonlighting proteins from the glycolytic pathway or TCA cycle can play roles in bacterial pathogens, either by acting as proteins secreted in a conventional pathway or not and/or as cell surface component that facilitate adhesion or adherence . This review outlines the multifuncionality exposed by a variety of Paracoccidioides spp. enzymes including aconitase, aldolase, glyceraldehyde-3-phosphate dehydrogenase, isocitrate lyase, malate synthase, triose phosphate isomerase, fumarase and enolase. The roles that moonlighting activities play in the virulence characteristics of this fungus and several other human pathogens during their interactions with the host are discussed.